IMPLEMENTASI MEDIA PEMBELAJARAN EKONOMI DALAM MEMAHAMI KONSEP ILMU EKONOMI DI SMA SRIJAYA NEGARA PALEMBANG - Siti Fatimah; Rusmin AR; Clara Ika Phaluphie (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study aims to harness the media's economic studies in understanding the concepts of economic science in the high schoo lstate Srijaya Palembang. The subject of research economics teacher as much as 4 teacher. Data collection using observation and documentation. The research results obtained the implementation of economic studies in understanding the concepts of economic science in the high school state Srijaya Palembang with criteria very good (85%), as seen from the planning of the learning process with criteria very good (80%) and the implementation of learning criteria very well (89%). The use of media of instruction on the implementation of the learning required of teachers in teaching, suggestion the implementation of learning activities from the outset, the core, and the cover should be presented first of all. Existing media utilized everything possible so that the process of learning achieved effective and efficient which is optimal.